Complementary and conventional providers in cancer care: experience of communication with patients and steps to improve communication with other providers - Trine Stub; Sara A. Quandt; Thomas A. Arcury; Joanne C. Sandberg; Agnete E. Kristoffersen (BMC, 2017)
Abstract Background Effective interdisciplinary communication is important to achieve better quality in health care. The aims of this study were to compare conventional and complementary providers' experience of communication about complementary therapies and conventional medicine with their cancer patients, and to investigate how they experience interdisciplinary communication and cooperation. Method This study analyzed data from a self-administrated questionnaire. A total of 606 different health care providers, from four counties in Norway, completed the questionnaire. The survey was developed to describe aspects of the communication pattern among oncology doctors, nurses, family physicians and complementary therapists (acupuncturists, massage therapists and reflexologists/zone-therapists). Between-group differences were analyzed using chi-square, ANOVA and Fisher's exact tests. Significance level was defined as p < 0.05 without adjustment for multiple comparisons. Result Conventional providers and complementary therapists had different patterns of communication with their cancer patients regarding complementary therapies. While complementary therapists advised their patients to apply both complementary and conventional modalities, medical doctors were less supportive of their patients' use of complementary therapies. Of conventional providers, nurses expressed more positive attitudes toward complementary therapies. Opportunities to improve communication between conventional and complementary providers were most strongly supported by complementary providers and nurses; medical doctors were less supportive of such attempts. A number of doctors showed lack of respect for complementary therapists, but asked for more research, guidelines for complementary modalities and training in conventional medicine for complementary therapists. Conclusion For better quality of care, greater communication about complementary therapy use is needed between cancer patients and their conventional and complementary providers. In addition, more communication between conventional and complementary providers is needed. Nurses may have a crucial role in facilitating communication, as they are positive toward complementary therapies and they have more direct communication with patients about their treatment preferences.